Pengaruh Baby SPA terhadap Kenaikan Berat Badan dan Perkembangan Bayi Umur 3-6 bulan - Sri Rahayu; Titi Suherni; Runjati Runjati (Pusat Penelitian dan Pengabdian kepada Masyarakat, Poltekkes Kemenkes Semarang, 2015)
The purpose of research was to analyze differences in body weight gain and development of infants aged 3-6 months. Type of study was pre-experimental research with Posttest Only Design. The population were infants aged 3-6 months who visited Ananda Home Birth in Ambarawa. The subjects were SPA treatment group and control respectively 17 babies by simple random sampling. Data collection used SPA treatment group 4 times for 8 weeks . Before and after measured weight gain and development with KPSP . Data were analyzed with the Mann Whitney test. The results mean score KPSP development of infants before and after the treatment group SPA was 8,12 into 9,59. The mean weight gain infants before and after the SPA was 5705 grams to 7188 grams. There was no differencess in development progress after the SPA between the treatment group and the control group and there were any differences the increase in weight gain between treatment and control groups (p value = 0.018 ). It is important for midwives to develop midwifery care to infants and toddlers with holistic care which one of them with a baby SPA.